Characteristics of men responding to an invitation to undergo testing for prostate cancer as part of a randomised trial. Issue 1 (December 2016) - Walsh, Eleanor; Turner, Emma; Lane, J.; Donovan, Jenny; Neal, David; Hamdy, Freddie; Martin, Richard
Abstract Background Sociodemographic characteristics are associated with participating in cancer screening and trials. We compared the characteristics of those responding with those not responding to a single invitation for prostate-specific antigen (PSA) testing for prostate cancer as part of the Cluster randomised triAl of PSA testing for Prostate cancer (CAP). Methods Age, rurality and deprivation among 197, 763 men from 271 cluster-randomised primary care centres in the UK were compared between those responding (n  = 90, 300) and those not responding (n  = 100, 953) to a prostate cancer testing invitation. Results There was little difference in age between responders and nonresponders. Responders were slightly more likely to come from urban rather than rural areas and were slightly less deprived than those who did not respond. Conclusion These data indicate similarities in age and only minor differences in deprivation and urban location between responders and nonresponders. These differences were smaller, but in the same direction as those observed in other screening trials. Trial registration ISRCTN92187251 . Registered on 29 November 2004.